1996
DOI: 10.1089/jop.1996.12.1
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Cyclosporine 1% in Artificial Tears

Abstract: We wished to determine the stability of frozen, refrigerated, and room temperature topical cyclosporine 1% in artificial tears (Tears Plus). Cyclosporine 1% eye drops were made in artificial tears prior to the manufacturers recommendations of using a lipid soluble vehicle, such as olive oil. Patients preferred the artificial tears preparation over the oil based cyclosporine product. Because of the good clinical response and the reluctance of patients to change to the oil vehicle product, we determined the stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Previous studies have evaluated the effect of refrigerating eye‐drops and its implication on various parameters such as drop stability and their ability to relieve symptoms upon instillation. A study by Fujishima et al revealed that participants were more comfortable with refrigerated artificial tears (preservative free Soft Santear, Santen Pharmaceutical Co., Osaka, Japan) at 4°C than room temperature or warmed to 36°C.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated the effect of refrigerating eye‐drops and its implication on various parameters such as drop stability and their ability to relieve symptoms upon instillation. A study by Fujishima et al revealed that participants were more comfortable with refrigerated artificial tears (preservative free Soft Santear, Santen Pharmaceutical Co., Osaka, Japan) at 4°C than room temperature or warmed to 36°C.…”
Section: Discussionmentioning
confidence: 99%
“…data, 2001). In this previous open study we had made 1% drops by adding 2 mL Cyclosporin injection 50 mg in 1 mL (Sandimmum, Novartis, Basel, Switzerland) to 8 mL of Tears Plus (Allergan, Irvine, CA, USA) 12 …”
Section: Introductionmentioning
confidence: 99%
“…In this previous open study we had made 1% drops by adding 2 mL Cyclosporin injection 50 mg in 1 mL (Sandimmum, Novartis, Basel, Switzerland) to 8 mL of Tears Plus (Allergan, Irvine, CA, USA). 12 Recently, Restasis (CsA 0.05%) has been made commercially available after Food and Drug Administration (USA) approval for treatment of dry eyes. This novel emulsion of CsA has been shown to have a good safety profile with no systemic side-effects.…”
Section: Introductionmentioning
confidence: 99%
“…CsA is itself very stable due to its lipophilic nature and its cyclic structure (Kumar et al, 2001). It was shown to be stable over 7 days at room temperature and up to 28 days at 4 • C when formulated at 1% in artificial tears (Fiscella et al, 1996). Although UNIL088 has a longer shelf-life at pH 5 than at pH 6 and 7, a neutral pH must be preferred for the formulation because of its biocompatibility.…”
Section: Discussionmentioning
confidence: 99%